Numerical Analysis of Prestressed Reinforced Concrete Beam Subjected to Blast Loading - Chen, Wensu; Hao, Hong; Chen, Shuyang (Elsevier, 2015)
Prestressing technique has been widely used in civilian and military constructions. The prestressed reinforced concrete (RC) structural components such as beams and columns usually outperform the non-prestressed RC components because prestressing not only increases the structural stiffness and load carrying capacity, but also has higher crack resistance than non-prestressed component. As a result, it usually leads to light structures. The investigation of non-prestressed RC components subjected to blast loadings has been reported in the literature. However, the study on the blast-resistant capacity of prestressed RC components is very limited. In this study, the dynamic response of a simply-supported prestressed RC beam with rectangular section under blast loadings is numerically investigated by using finite element codes LS-DYNA. The prestress is pre-applied on the RC beam in an analytical approach. The reliability of the numerical model is calibrated with testing results available in the literature. With the calibrated model, numerical simulations on four groups of prestressed RC beams to blast loadings are carried out to investigate the influences of prestressing level and concreted compressive strength on beam blast loading resistance capacity. The structural responses such as mid-span maximum deflection, residual deflection, cracking, stress of rebars and shear stress of concrete near the supports are extracted from the numerical results. The effectiveness of prestressing on blast-resistant capacity of RC beam is demonstrated through comparing the results with the bench marking non-prestressed RC beam under the same blast loadings.